A nano-Fe 0 @Fe3O4 core-shell structure material and its preparation method and use

By forming a dense Fe3O4 shell on nano zero-valent iron, the problem of complex and high cost of preparation process of nano Fe0@Fe3O4 composite materials is solved, its antioxidant performance and activation efficiency are improved, and the effect of efficient degradation of organic pollutants is achieved. .

CN114618493BActive Publication Date: 2024-12-13INST OF URBAN ENVIRONMENT CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210342868.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2024-12-13
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

The preparation process of existing nano-Fe0@Fe3O4 composite materials is complex, the conditions are harsh, the preparation cost is high, and the nano-zero-valent iron is easy to oxidize, making activation performance difficult to maintain.

Method used

Strong alkali and strong reducing agent are mixed in ultrapure water to form an iron salt solution, and nano zero-valent iron is generated under heating and stirring conditions. Then, a dense Fe3O4 shell is formed through hydrothermal reaction, forming a nano Fe0@Fe3O4 core shell. Structural material.

Benefits of technology

The antioxidation of nano zero-valent iron is achieved, and its efficiency in activating persulfates to degrade organic pollutants is improved. The preparation process is simplified, the cost is reduced, and it has good economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003575528780000011
    Figure HDA0003575528780000011
  • Figure HDA0003575528780000012
    Figure HDA0003575528780000012
  • Figure HDA0003575528780000021
    Figure HDA0003575528780000021
Patent Text Reader

Abstract

The present invention relates to a nano-Fe 0 @Fe3O4 core-shell structure material and its preparation method and application. The method comprises the following steps: firstly preparing a mixture of a strong base and a strong reducing agent and an iron salt solution, then adding the mixture of the strong base and the strong reducing agent to the iron salt solution, and continuously stirring to obtain nano zero-valent iron (Fe 0 ) suspension, and then heating the nano zero-valent iron suspension to 80°C, maintaining constant temperature and stirring continuously, after sufficient reaction, obtaining black solid particles, separating the generated black solid particles by magnetic separation, and finally washing with deionized water three times, and drying with low-temperature blast air to obtain nano Fe 0 @Fe3O4 core-shell structure material. The nano-Fe prepared by the present invention 0 @Fe3O4 core-shell structure material can effectively activate persulfate to degrade organic pollutants in water, and better solve the problems of nano zero-valent iron being easily oxidized in practical applications and difficulty in maintaining activation performance. At the same time, compared with the prior art, the nano Fe 0 The preparation method of the Fe3O4 core-shell structure material has the advantages of novelty, easy availability of required raw materials, simple process, low cost, etc. 0 @Fe3O4 core-shell structure materials have good economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental composite materials, and specifically relates to a nano-Fe 0 @Fe3O4 core-shell structure material and its preparation method and use. Background Art

[0002] With the rapid advancement of industrialization and urbanization, the types and quantities of compounds discharged into the environment are increasing each year, and the environmental pollution problems caused cannot be ignored. Among them, persistent organic pollutants have the characteristics of high toxicity, high bioaccumulation and difficulty in degradation, which seriously threaten ecological security and public health. Therefore, it is urgent to develop an efficient, low-cost and green and environmentally friendly governance technology.

[0003] In recent years, advanced oxidation technology based on sulfate radicals has attracted wide attention as an emerging in-situ chemical oxidation remediation technology due to its high efficiency in degradation of organic pollutants and high adaptability. The persulfate can be effectively activated to produce sulfate radicals (SO4 ·ˉ ), thereby oxidizing and degrading organic pollutants. Iron-based heterogeneous activators have the advantages of wide sources, low cost, environmental friendliness, and easy separation and recovery, and are widely used in the activation of persulfate. Among them, nano zero-valent iron has a small particle size, a large specific surface area, and a high reaction activity. It can efficiently activate persulfate and degrade difficult-to-degrade organic pollutants. However, nano zero-valent iron has the defects of easy agglomeration, low antioxidant capacity, and difficulty in storage and transportation, which greatly limits its application in advanced oxidation technology. In order to solve this problem, nano zero-valent iron needs to be modified. The current common modification methods include: introducing a second metal to form a bimetallic composite nano zero-valent iron; loading nano zero-valent iron on the surface of a solid carrier to form a loaded nano zero-valent iron; adding a surfactant to modify the surface of nano zero-valent iron and synthesizing nano zero-valent iron / nano ferroferric oxide composite materials.

[0004] Ferroferric oxide has good stability. Using ferroferric oxide to wrap nano zero-valent iron can effectively improve the antioxidant capacity of nano zero-valent iron. At the same time, the trans-spinel structure of ferroferric oxide can stably accommodate Fe 2+ with Fe 3+ , making it easy to achieve electron transfer, thus not reducing the catalytic activity of nano zero-valent iron. 0 @The preparation method of Fe3O4 composite materials has the disadvantages of high material preparation conditions, complex operation and high preparation cost.

[0005] Invention patent CN105771148A discloses a nano-Fe 0The preparation method of the Fe3O4 composite material is to firstly react an iron salt solution with ammonia water to prepare nano Fe3O4, then disperse the nano Fe3O4 in water and remix it with a divalent iron salt solution, and then drop a reducing agent solution into the mixed solution to obtain nano Fe 0 @Fe3O4 composite material. The nano-Fe prepared by this method 0 @Fe3O4 composite material does not have a Fe3O4 shell on its surface and still has the problem of easy oxidation, so it needs to be dispersed in water for preservation.

[0006] Invention patent application CN112875773A discloses a method for preparing a surface-modified magnetic nano zero-valent iron composite material, in which a nano zero-valent iron suspension is mixed with an alkaline precipitant under vacuum conditions for co-precipitation reaction, thereby obtaining a surface-modified magnetic nano zero-valent iron composite material having an Fe3O4 oxide protective film. This method needs to be carried out under vacuum conditions, has high requirements for preparation conditions, is difficult to operate, has high costs, and is not easy to scale up industrially.

[0007] Invention patent CN103341165B discloses a method for preparing composite Fe@Fe3O4 nanoparticles. The method first uses octadecene as a solvent, Fe(CO)5 as an iron source, oleylamine as a surfactant and stabilizer, and a high-temperature pyrolysis method to prepare Fe nanomaterials with good dispersibility. Then, (CH3)3NO is used as an oxidant to oxidize a layer of Fe3O4 on the Fe surface at high temperature, and dopamine connected with polyethylene glycol monocarboxylic acid is used as a ligand to improve water solubility, thereby obtaining a magnetic nanocomposite material with high magnetization intensity and obvious photothermal effect. This method has many raw materials and high costs, a complex preparation process, and a high reaction temperature and high energy consumption. In addition, this method uses a variety of organic reagents, which does not conform to the current concept of green environmental protection.

[0008] Therefore, how to solve the problem of easy oxidation of nano zero-valent iron and nano Fe 0 The complex preparation process and harsh conditions of @Fe3O4 composite materials, as well as the high preparation cost, have become a huge challenge currently faced by this field. Summary of the invention

[0009] The present invention is aimed at the nano-Fe 0 The preparation process of Fe3O4 composite materials is complex and the conditions are harsh, and the preparation cost is high. 0 @Preparation method and application of Fe3O4 core-shell structure material.

[0010] The present invention aims to provide a nano-Fe 0 @Fe3O4 core-shell structure material and its preparation method, this nano-Fe 0@Fe3O4 core-shell structure material can effectively activate persulfate to degrade organic pollutants in solution, and can better solve the problems of nano zero-valent iron being easily oxidized in practical applications and difficulty in maintaining activation performance. At the same time, compared with the prior art, the nano Fe 0 The preparation method of the Fe3O4 core-shell structure material has the advantages of novelty, easy availability of required raw materials, simple process, low cost, etc. 0 @Fe3O4 core-shell structure materials have good economic and environmental benefits.

[0011] To achieve the purpose of the present invention, the following technical solutions are adopted:

[0012] A nano-Fe 0 The preparation method of the @Fe3O4 core-shell structure material comprises the following steps:

[0013] (1) dissolving a strong base and a strong reducing agent in ultrapure water, and mixing them thoroughly to obtain a mixture of a strong base and a strong reducing agent; dissolving an iron salt in ultrapure water to obtain an iron salt solution; and then adding the mixture of a strong base and a strong reducing agent dropwise to the iron salt solution, and stirring to obtain nano zero-valent iron (Fe 0 ) suspension;

[0014] (2) heating the nano zero-valent iron suspension to 60-90° C. and continuously stirring the suspension to obtain black solid particles after sufficient reaction;

[0015] (3) The black solid particles were separated by magnetic separation, washed three times with deionized water, and dried to obtain nano-Fe 0 @Fe3O4 core-shell structure material.

[0016] Preferably, the iron salt is selected from a ferrous salt and a ferric salt. The ferrous salt is any one of ferrous chloride, ferrous nitrate or ferrous sulfate; the ferric salt is any one of ferric nitrate, ferric sulfate, ferric chloride or ferric acetate.

[0017] Preferably, the strong reducing agent is potassium borohydride or sodium borohydride.

[0018] Preferably, the strong base is sodium hydroxide or potassium hydroxide.

[0019] Preferably, the iron salt is ferrous sulfate, the strong reducing agent is sodium borohydride, the strong base is sodium hydroxide, and the molar ratio of the iron salt, the strong reducing agent and the strong base solution is 1:2:3.

[0020] Preferably, the heating method is water bath heating, the stirring method is horizontal oscillation, the oscillation rate is 180r / min, and the heating process is from room temperature to 80°C, and then kept at 80°C for 2 hours.

[0021] In the present invention, the nano zero-valent iron undergoes the following reaction during the heating and stirring process:

[0022] 2Fe+O2+2H2O=2Fe(OH)2

[0023] 6Fe(OH)2+O2=2Fe3O4+6H2O

[0024] The generated Fe3O4 adheres to the surface of nano-zero-valent iron, thus forming a dense Fe3O4 shell.

[0025] After the hydrothermal reaction is completed, the present invention preferably uses a magnetic separation method to separate the black solid particles produced by the hydrothermal reaction into solid and liquid, and washes them with deionized water for 3 times, and then dries them to obtain nano-Fe 0 @Fe3O4 core-shell structure material. The present invention has no special requirements for the drying. Preferably, the washed black solid particles are placed in a blast drying oven and dried at 45°C for 12 hours.

[0026] The present invention also protects the use of a nano Fe 0 Preparation method of Fe3O4 core-shell structure material 0 @Fe3O4 core-shell structure material.

[0027] The present invention also protects the nano Fe 0 @Fe3O4 core-shell structure material is used to activate persulfate to degrade organic pollutants in solution, or to treat hexavalent chromium (Cr 6+ ), or for soil remediation.

[0028] Further, the nano-Fe 0 @Fe3O4 core-shell structure material and persulfate are added to 1mg / L organic solution at a ratio of 0.05-0.4g / L and 0.25-4mmol / L respectively, and the removal rate of organic pollutants can reach more than 90%.

[0029] Optionally, the persulfate is sodium persulfate.

[0030] Optionally, the organic pollutant is phenanthrene, a typical polycyclic aromatic hydrocarbon monomer.

[0031] Beneficial effect: The present invention firstly uses a strong reducing agent to reduce an iron source under alkaline conditions to prepare nanometer zero-valent iron, and then the nanometer zero-valent iron reacts with H2O and O2 under hydrothermal conditions to generate Fe(OH)2, and then Fe(OH)2 and O2 react to generate Fe3O4, and the generated Fe3O4 adheres to the surface of the nanometer zero-valent iron, thereby forming a dense Fe3O4 shell layer, and obtaining nanometer Fe 0@Fe3O4 core-shell structure material. The dense Fe3O4 shell layer can make the nano zero-valent iron not easily oxidized. The nano Fe prepared by the present invention 0 @Fe3O4 core-shell structure material can efficiently activate persulfate to degrade organic pollutants, and can solve the problem of low activation efficiency when nano zero-valent iron is used as PS activator. At the same time, compared with the prior art, the nano Fe 0 The preparation method of the Fe3O4 core-shell structure material has the advantages of novelty, easy availability of required raw materials, simple process, low cost, etc. 0 @Fe3O4 core-shell structure material has good economic and environmental benefits. This method can also be further applied to soil and groundwater pollution remediation. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the Fe of Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 Scanning electron microscope image of Fe3O4 of Comparative Example 2.

[0033] Figure 2 is the Fe of Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 Compared with the X-ray diffraction pattern of Fe3O4 in Comparative Example 2.

[0034] Figure 3 is the Fe of Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 Comparison chart of H2 production content from the reaction of Fe3O4 and sulfuric acid in Comparative Example 2.

[0035] Figure 4 is the Fe of Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 Transmission electron microscope image of Fe3O4 of Comparative Example 2.

[0036] Figure 5 is the Fe of Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 Comparison of the effect of Fe3O4-activated persulfate in degrading phenanthrene in aqueous solution in Comparative Example 2.

[0037] Figure 6 Nano-Fe 0 @Chart of PS concentration changes during the degradation of phenanthrene by persulfate activated by Fe3O4 core-shell structure material.

[0038] Figure 7 Nano-Fe 0@Fe3O4 core-shell structure material activation persulfate degradation of phenanthrene 2+ Concentration variation graph.

[0039] Figure 8 Nano-Fe 0 @Fe3O4 core-shell structure material and nano-Fe after storage in air for 60 days 0 @Comparison of the effects of Fe3O4 core-shell structure materials activating persulfate to degrade phenanthrene in aqueous solution. DETAILED DESCRIPTION

[0040] In order to better explain the present invention, the present invention is further described in conjunction with the following specific embodiments and drawings.

[0041] Note that the following examples are only intended to help understand the present invention, but are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the scientific terms used in the examples and comparative examples have the same meanings as those commonly understood by those skilled in the art, the operating techniques used are all conventional techniques, and the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0042] Example 1

[0043] A nano-Fe 0 The preparation method of the @Fe3O4 core-shell structure material comprises the following specific steps:

[0044] Weigh 0.01 mol of FeSO4·7H2O and dissolve it in 100 mL of ultrapure water to obtain a FeSO4 solution. At the same time, weigh 0.02 mol of NaBH4 and 0.03 mol of NaOH and dissolve them in 50 mL of ultrapure water to obtain a mixed solution of NaBH4 and NaOH, add the mixed solution dropwise to the FeSO4 solution, stir evenly, and allow it to react fully to obtain a nano zero-valent iron suspension. Place the nano zero-valent iron suspension in a water bath shaker, heat to 80°C, maintain for 2 hours, and continue to oscillate at a rate of 180 r / min. After the reaction is completed, collect the generated black solid particles by magnetic separation, wash them several times with deionized water, and place them in a 45°C forced air drying oven to dry for 12 hours to obtain nano Fe 0 @Fe3O4 core-shell structure material.

[0045] Comparative Example 1

[0046] A nanometer zero-valent iron (Fe 0 ), the specific steps are as follows:

[0047] Weigh 0.01 mol of FeSO4·7H2O and dissolve it in 100 mL of ultrapure water to obtain a FeSO4 solution. At the same time, weigh 0.02 mol of NaBH4 and 0.01 mol of NaOH and dissolve them in 50 mL of ultrapure water to obtain a mixed solution of NaBH4 and NaOH. Add the mixed solution dropwise to the FeSO4 solution, stir evenly, and react fully until no obvious hydrogen is generated to obtain a nano zero-valent iron suspension. Collect the generated black solid particles using magnetic separation, wash them several times with deionized water, and freeze-dry them for 48 hours to obtain nano zero-valent iron.

[0048] Comparative Example 2

[0049] A method for preparing ferroferric oxide (Fe3O4), the specific steps are as follows:

[0050] Weigh 0.01 mol of FeSO4·7H2O and dissolve it in 100 mL of ultrapure water to obtain FeSO4 solution. At the same time, weigh 0.02 mol of NaOH and dissolve it in 50 mL of ultrapure water to obtain NaOH solution. Add the NaOH solution to the FeSO4 solution, stir evenly, and then place it in a water bath shaker, heat it to 80°C, keep it for 2 hours, and continue to shake. Collect the generated black solid particles using magnetic separation, wash them with deionized water several times, and place them in a 65°C forced air drying oven to dry for 12 hours to obtain ferroferric oxide.

[0051] The nano-Fe prepared in Example 1 of the present invention 0 @Fe3O4 core-shell structure material, nano zero-valent iron (Fe 0 ) and the iron oxide (Fe3O4) prepared in Comparative Example 2 were characterized by scanning electron microscopy, and the results showed that ( Figure 1 ), nano-Fe 0 The morphology of the Fe3O4 core-shell structure material is different from that of Fe 0 and Fe3O4 particles, which mainly present octahedral morphology, with particle size close to that of Fe3O4 particles, and their agglomeration phenomenon is more 0 Somewhat alleviated.

[0052] The nano-Fe prepared in Example 1 of the present invention 0 @Fe3O4 core-shell structure material, nano zero-valent iron (Fe 0 ) and the iron oxide (Fe3O4) prepared in Comparative Example 2 were subjected to X-ray diffraction characterization analysis, and the results showed that ( Figure 2 ), nano-Fe 0@Fe3O4 core-shell structure material has a similar crystal structure to Fe3O4, with characteristic diffraction peaks of Fe3O4 at 18.3°(200), 30.2°(220), 35.8°(311), 43.6°(400), 53.6°(422), 57.3°(511) and 64.1°(440), indicating that nano-Fe 0 @Fe3O4 core-shell structure material has Fe3O4 crystal phase. 0 There is a weak broad peak at 2θ = 44.7°, indicating that Fe 0 It has been successfully prepared, but the crystallinity is poor. 0 No obvious Fe was observed in the spectrum of the Fe3O4 core-shell structure material 0 The peak of nano-Fe 0 @Nano zero-valent iron in the Fe3O4 core-shell structure may exist mainly in an amorphous form.

[0053] 0.1 g of nano-Fe prepared in Example 1 of the present invention 0 @Fe3O4 core-shell structure material, 0.02g nano zero-valent iron (Fe 0 ) and 0.02g of ferroferric oxide (Fe3O4) prepared in Comparative Example 2 were reacted with 10mL of 3M sulfuric acid, and the amount of H2 generated during each reaction was measured. The results showed that ( Figure 3 ), Fe3O4 reacts with sulfuric acid without producing H2, but Fe 0 and nano-Fe 0 @Fe3O4 core-shell structure reacts with sulfuric acid to produce H2, proving that nano-Fe 0 @There is a zero-valent iron component in the Fe3O4 core-shell structure.

[0054] The nano-Fe prepared in Example 1 of the present invention 0 @Fe3O4 core-shell structure material was characterized by transmission electron microscopy, and the results showed that ( Figure 4 ), the material presents Fe 0 The core-shell structure is a core with a Fe3O4 shell layer. In the HRTEM analysis, Fe 0 The diffraction fringes of Fe3O4 and Fe3O4 have lattice spacings of 0.21nm (110) and 0.30nm (220), respectively, proving that the material synthesized in the present invention is a nano-Fe 0 @Fe3O4 core-shell structure material.

[0055] The above results show that the present invention successfully synthesized a nano-Fe 0 @Fe3O4 core-shell structure material.

[0056] Example 2

[0057] Investigation of nano-Fe 0 @The effect of Fe3O4 core-shell structure material on activating persulfate (PS) to degrade organic pollutants.

[0058] Phenanthrene was selected as a typical organic pollutant, and the nano-Fe prepared in Example 1 of the present invention was 0 @Fe3O4 core-shell structure material, nano zero-valent iron (Fe 0 ) and the ferroferric oxide (Fe3O4) material prepared in Comparative Example 2 were used to activate PS to degrade phenanthrene in aqueous solution to evaluate the effect of nano-Fe 0 @Fe3O4 core-shell structure material activates PS to degrade organic pollutants. The specific steps are as follows: weigh 0.03g of Fe in Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 The Fe3O4 in Comparative Example 2 was added to a 90 mL 1 mg / L phenanthrene aqueous solution, and then 10 mL 20 mM PS solution was added to trigger the reaction. The reaction time was 1 h. During the reaction, 1 mL of the reaction solution was taken out and mixed with 1 mL of methanol solution at 10 min, 20 min, 30 min, 40 min, 50 min and 60 min to terminate the reaction. The mixed solution was then filtered and the phenanthrene content in the sample was determined by HPLC. The degradation effects of phenanthrene in different treatment groups are shown in Figure 2. Figure 5 As shown, the results show that compared with Fe 0 / PS, Fe3O 4 / PS treatment group, Fe 0 The degradation efficiency of phenanthrene in the @Fe3O4 / PS treatment group was significantly higher than that in Fe 0 / PS and Fe3O 4 / In the PS treatment group, after 60 minutes of reaction, the degradation rate of phenanthrene can reach 93.49%. 0 @Fe3O4 core-shell structure materials can effectively activate PS to degrade organic pollutants.

[0059] Example 3

[0060] Investigation of nano-Fe 0 @The decomposition efficiency of PS during the activation of PS by Fe3O4 core-shell structure material to degrade phenanthrene.

[0061] Phenanthrene was selected as a typical organic pollutant, and the nano-Fe prepared in Example 1 of the present invention was 0 @Fe3O4 core-shell structure material, nano zero-valent iron (Fe 0 ) and the ferroferric oxide (Fe3O4) material prepared in Comparative Example 2 were used in the persulfate system to treat and degrade the phenanthrene-contaminated aqueous solution, and the nano-Fe0 @Fe3O4 core-shell structure materials, nano zero-valent iron (Fe 0 ) and ferroferric oxide (Fe3O4) during the application process. The specific steps are as follows: weigh 0.03g of Fe in Example 1 0 @Fe3O4, Fe in Comparative Example 1 0 The Fe3O4 in Comparative Example 2 was added to a 90 mL phenanthrene aqueous solution with a concentration of 1 mg / L, and then 10 mL 20 mM PS solution was added to trigger the reaction. The reaction time was 1 h. During the reaction, 0.1 mL of the reaction solution was taken out at 10 min, 20 min, 30 min, 40 min, 50 min and 60 min, 0.2 g sodium bicarbonate and 4 g potassium iodide solid were added to the 0.1 mL reaction solution, and ultrapure water was added to dilute to 5 mL. The mixture was shaken well, and the PS concentration in the sample was determined by a UV-visible spectrophotometer after 10 min of color development. The results of PS concentration changes in different systems are shown in Figure 2. Figure 6 As shown, the results show that in Fe 0 In the / PS system, the PS concentration dropped sharply at the beginning of the reaction, indicating that Fe 0 After the reaction with PS is triggered, a large amount of PS is activated and decomposed in a short time. In the Fe3O4 / PS system, as the reaction proceeds, the PS concentration remains basically unchanged, indicating that PS cannot be effectively activated. 0 In the @Fe3O4 / PS system, the concentration of PS showed a gradual downward trend and eventually stabilized, indicating that PS was gradually activated and decomposed during the reaction. 0 @The process of activating PS by Fe3O4 is relatively slow, which can improve the utilization efficiency of PS and thus improve the degradation efficiency of organic pollutants.

[0062] Example 4

[0063] Investigation of nano-Fe 0 @Fe3O4 core-shell structure material activation PS degradation process Fe 2+ Concentration changes.

[0064] Phenanthrene was selected as a typical organic pollutant, and the nano-Fe prepared in Example 1 of the present invention was 0 @Fe3O4 core-shell structure material, nano zero-valent iron (Fe 0 ) and the ferroferric oxide (Fe3O4) material prepared in Comparative Example 2 were used in the persulfate system to treat and degrade the phenanthrene-contaminated aqueous solution, and the nano-Fe 0 @Fe3O4 core-shell structure materials, nano zero-valent iron (Fe 0 ) and ferroferric oxide (Fe3O4) in the application process 2+The specific steps are as follows: weigh 0.03g of Fe 0 @Fe3O4, Fe in Comparative Example 1 0 The Fe3O4 in Comparative Example 2 was added to a 90 mL phenanthroline aqueous solution with a concentration of 1 mg / L, and then 10 mL 20 mM PS solution was added to trigger the reaction. The reaction time was 1 h. During the reaction, 1 mL of the reaction solution was taken out at 10 min, 20 min, 30 min, 40 min, 50 min and 60 min, and 1 mL of the reaction solution was added with 1 mL 0.5% o-phenanthroline solution and 1 mL buffer solution, shaken well, and after color development for 10 min, the Fe in the sample was determined using a UV-visible spectrophotometer. 2+ Concentration. Different systems Fe 2+ The concentration changes are as follows Figure 7 As shown, the results show that in Fe 0 In the / PS system, Fe 2+ The concentration increased rapidly at the beginning of the reaction and then remained stable, and the concentration was high, indicating that Fe 0 A large amount of Fe is released immediately after the reaction with PS is triggered 2+ , which consumes a large amount of PS immediately after activation, but due to Fe 0 Excess Fe is released in the initial stage of the reaction 2+ The SO4·ˉ is quenched, resulting in poor degradation of phenanthrene by the system. In the Fe3O4 / PS system, as the reaction proceeds, Fe 2+ The concentration increased slightly, indicating that Fe3O4 released Fe 2+ The content is low, so PS cannot be effectively activated. 0 In the @Fe3O4 / PS system, Fe 2+ The concentration of Fe 0 @Fe3O4 slowly releases Fe during the reaction 2+ , gradually activating PS, thereby improving the degradation efficiency of organic pollutants, which is consistent with the experimental results of Example 3.

[0065] Example 5

[0066] Investigation of nano-Fe 0 @Antioxidation properties of Fe3O4 core-shell structure materials.

[0067] Phenanthrene was selected as a typical organic pollutant, and the nano-Fe 0 @Fe3O4 core-shell structure material and nano-Fe after being exposed to air and stored at room temperature and humidity for 60 days 0 @Fe3O4 core-shell structure material (Fe 0@Fe3O4-60 d) was used in the persulfate system to treat and degrade phenanthrene-contaminated aqueous solution, and the nano-Fe 0 @Fe3O4 core-shell structure material oxidation resistance. The specific steps are as follows: weigh 0.03g of the newly prepared nano-Fe 0 @Fe3O4 core-shell structure material and nano-Fe after being exposed to air and stored at room temperature and humidity for 60 days 0 @Fe3O4 core-shell structure material (Fe 0 @Fe3O4-60 d) was added to a 90 mL 1 mg / L phenanthrene aqueous solution, and then 10 mL 20 mM PS solution was added to trigger the reaction. After 1 h of reaction, 1 mL of the reaction solution was taken out and mixed with 1 mL of methanol solution to terminate the reaction. The mixed solution was then filtered and the phenanthrene content in the sample was determined by HPLC. The results are shown in Figure 8 As shown, Fe 0 The degradation efficiency of phenanthrene by @Fe3O4-60 d / PS system is 89.5%, slightly lower than that of Fe 0 @Fe3O4 / PS treatment group, showing that after being exposed to air and stored at room temperature and humidity for 60 days, Fe 0 @Fe3O4 has no significant change in the activation performance of PS. 0 @Fe3O4 core-shell structure material has good anti-oxidation properties.

[0068] The above is only a preferred embodiment of the present invention, but the present invention is not limited to the above embodiment. Those skilled in the art should understand that any improvement, addition, deletion, modification, equivalent replacement, etc. made without departing from the spirit and technical principle of the present invention are still within the protection scope of the present invention.

Claims

1. A nano-Fe 0 @The application of Fe3O4 core-shell structure material is characterized by: (1) The nano-Fe 0 The preparation method of the Fe3O4 core-shell structure material is as follows: sodium hydroxide and sodium borohydride are dissolved in ultrapure water, and the mixture is fully mixed to obtain a sodium hydroxide and sodium borohydride mixed solution; ferrous sulfate is dissolved in ultrapure water to obtain a ferrous sulfate solution; and then the sodium hydroxide and sodium borohydride mixed solution is added dropwise to the ferrous sulfate solution, and stirred evenly to obtain nano zero-valent iron (Fe 0 ) suspension, heating the nano zero-valent iron suspension from room temperature to a constant temperature in a water bath and continuously stirring, after sufficient reaction, obtaining black solid particles, separating the generated black solid particles by magnetic separation, washing with deionized water three times, and drying at low temperature of 45-65 ° C for 12 hours to obtain nano Fe 0 @Fe3O4 core-shell structure material; the molar ratio of ferrous sulfate, sodium borohydride and sodium hydroxide solution is 1:2:3, heated in a water bath to a constant temperature of 60-90 °C, and the constant temperature is maintained for 2-4 h; (2) the prepared nano-Fe 0 @Fe3O4 core-shell structure material is used to activate persulfate to degrade organic pollutants in solution, characterized by nano-Fe 0 When Fe3O4 core-shell structure material and persulfate are added to a 1 mg / L organic solution at a ratio of 0.05-0.4 g / L and 0.25-4 mmol / L, respectively, the removal rate of organic pollutants can reach more than 90%; (3) The organic pollutants are polycyclic aromatic hydrocarbons.

2. Nano Fe according to claim 1 0 @The application of Fe3O4 core-shell structure material is characterized by: The persulfate is sodium persulfate or sodium peroxymonosulfate.